AB0925 MULTIPLE FRACTURES DUE TO IRON-INDUCED AND FGF23-MEDIATED HYPOPHOSPHATAEMIC OSTEOMALACIA: AN UNKNOWN ADVERSE EFFECT. (2nd June 2020) - Fernández, E.; Tornero, C.; Navarro-Compán, V.; Bonilla, G.; Plasencia, C.; Balsa, A.; Aguado, P.
Abstract : Background: The use of a specific and widely used type of intravenous ferrotherapy, ferric carboxymaltose (FCM), has been linked to the development of an asymptomatic and transient hypophosphataemia. However, in recent years it has been published that it can generate a severe hypophosphataemic osteomalacia (HPO) mediated by fibroblast growth factor 23 (FGF23) that is associated with high morbidity 1 . It is a potentially serious adverse effect whose prevalence is unknown and that clinicians may know little about. Objectives: To know the clinical and biochemical characteristics of this adverse effect and make it visible in the medical community. Methods: Observational descriptive study of three cases of patients assessed in the Rheumatology department of our hospital who were referred for study of recurrent fractures and diagnosed of FGF23-mediated HPO due to FCM. Demographic, clinical and laboratory data of the patients are described. Results: The clinical and laboratory characteristics of the patients are shown in table 1 . All patients presented clinical and biochemical features compatible with FGF23-mediated HPO (mean of FGF levels 240 kRU/L, NR 0-145). All had multiple insufficiency fractures (Fx) and/or avascular necrosis (AN), with hip involvement in all 3 cases. Other causes of HPO were ruled out in all of them using PET 18 F-FDG, octreotide scintigraphy, abdominal magnetic resonance and PET 68 Ga-DOTATOC, and a genetic study of hypophosphataemic rickets was also performed in case 1. In all patients FCM was discontinued and phosphate levels were progressively normalized allowing the withdrawal of oral phosphate and calcitriol replacement therapy. After metabolic normalization, none presented new Fx or AN. Conclusion: Treatment with FCM can cause severe FGF23-mediated HPO, multiple fractures and a great decrease in the quality of life. Since it can be potentially serious and easily reversible, it is important to favor the dissemination of these new cases and the knowledge of this disease. The need to monitor phosphate and/or FGF23 levels in patients receiving this intravenous iron therapy should be evaluated. References: [1]Bishay RH, Ganda K, Seibel MJ. Long-term iron polymaltose infusions associated with hypophosphataemic osteomalacia: a report of two cases and review of the literature. Ther Adv Endocrinol Metab. 2017;8(1-2):14–19. doi:10.1177/2042018816678363 Disclosure of Interests: Elisa Fernández: None declared, Carolina Tornero: None declared, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB, Gemma Bonilla: None declared, Chamaida Plasencia: None declared, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz, Pilar Aguado: None declared